Betulinic acid inhibits growth of cultured vascular smooth muscle cells in vitro by inducing G1 arrest and apoptosis - Abd Manaf, Ali; Raja Kumar, Vadivelu; Swee, Keong Yeap; Muhajir, Hamid (2012)
Betulinic acid inhibits growth of cultured vascular smooth muscle cells in vitro by inducing G1 arrest and apoptosis (Article) Vadivelu, R.K.a u, Yeap, S.K.a g2, Ali, A.M.b erd, Hamid, M.c u, Alitheen, N.B.d it a Institute of Bioscience, Universiti Putra Malaysia, Selangor, Serdang, Malaysia b Faculty of Agriculture and Biotechnology, Universiti Sultan Zainal Abidin, Kampus Kota, Jalan Sultan Mahmud, 20400 Kuala Terengganu, Malaysia Department of Microbiology, Faculty of Biotechnology and Biomolecular Sciences, Universiti Putra Malaysia, Selangor, 43400 Serdang, Malaysia View additional affiliations Abstract V View references (30) Betulinic acid is a widely available plant-derived triterpene which is reported to possess selective cytotoxic activity against cancer cells of neuroectodermal origin and leukemia. However, the potential of betulinic acid as an antiproliferative and cytotoxic agent on vascular smooth muscle (VSMC) is still unclear. This study was carried out to demonstrate the antiproliferative and cytotoxic effect of betulinic acid on VSMCs using 3-[4,5-dimethylthizol-2- y11-2,5-diphenyltetrazolium bromide (MTT) assay, flow cytometry cell cycle assay, BrdU proliferation assay, acridine orange/propidium iodide staining, and comet assay. Result from MTT and BrdU assays indicated that betulinic acid was able to inhibit the growth and proliferation of VSMCs in a dose-dependent manner with IC50 of 18 g/mL significantly (13<0.05). Nevertheless, betulinic acid exhibited G1 cell cycle arrest in flow cytometry cell cycle profiling and low level of DNA damage against VSMC in acridine orange/propidium iodide and comet assay after 24 h of treatment. In conclusion, betulinic acid induced Gi cell cycle arrest and dose-dependent DNA damage on VSMC. 2012 Raja Kumar Vadivelu et al. Reaxys Database Information